Logic Circuit Visualization - Markovski, Jasen; Mishev, Anastas; Gushev, Marjan (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2001)
There are a lot of tools for logic circuit design and presentation. These applications have a lot of features, although they can be applied after the user draws the circuit. In this article we give an algorithm for logic circuit visualization for known connections between the elements. The logic circuit is defined by the connections between the elements regardless the circuit type. The algorithm is presented by flowchart and its application in real world application is shown.
Keywords: logic circuit, visualization technique, simulation, signal flow